Development of Interactive Augmented Reality Cards as a Learning Media for the Solar System in Space Adventure Games for Grade VI Elementary Schools - Awalia Anzilni; Hafizah Ghany Hayudinna (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2025)
Abstract: Elementary school children are at the concrete operational stage so they need learning media such as Augmented Reality (AR) to understand abstract material. At SD Negeri 01 Gumawang, despite having the potential to use technology, teachers still have limitations in innovation and implementing effective learning media. This study aims to develop an interactive AR through the "Space Adventure" game method to provide a more concrete learning experience through innovative and fun learning. This research uses the research and development (R&D) method with the ADDIE development model consisting of five stages, namely analysis, design, development, implementation, and evaluation. The data in this study were collected through interviews, observation, media validation, and practicality testing media, as well as documentation, with descriptive analysis, both qualitative and quantitative. The results of the interactive AR card development research obtained a validation score of 86% of the material experts with a very suitable category and a score of 91,28% of media experts with a very suitable category. Then according to the questionnaire's responses, two teachers received a score of 86,87% and 94,37% with a very applicable category. The application of this game increases the interests and competitiveness of students in participating in learning. Abstrak: Anak-anak sekolah dasar berada pada tahap operasional konkret sehingga mereka membutuhkan media pembelajaran seperti Augmented Reality (AR) untuk memahami materi yang bersifat abstrak. Di SD Negeri 01 Gumawang, meskipun memiliki potensi untuk menggunakan teknologi, guru masih memiliki keterbatasan dalam berinovasi dan menerapkan media pembelajaran yang efektif. Penelitian ini bertujuan untuk mengembangkan media pembelajaran interaktif berbasis AR melalui metode permainan "Space Adventure" guna memberikan pengalaman belajar yang lebih konkret melalui pembelajaran yang inovatif dan menyenangkan. Penelitian ini menggunakan metode penelitian dan pengembangan (R&D) dengan model pengembangan ADDIE yang terdiri dari lima tahap, yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Data dalam penelitian ini dikumpulkan melalui wawancara, observasi, validasi media, uji kepraktisan media, serta dokumentasi, dengan analisis deskriptif, baik kualitatif maupun kuantitatif. Hasil penelitian pengembangan kartu AR interaktif memperoleh skor validasi sebesar 86% dari ahli materi dengan kategori sangat layak dan skor 91,28% dari ahli media dengan kategori sangat layak. Kemudian berdasarkan respons angket, dua orang guru memberikan skor sebesar 86,87% dan 94,37% dengan kategori sangat praktis. Penerapan permainan ini meningkatkan minat dan daya saing siswa dalam mengikuti pembelajaran.